The value of social media tool for monitoring and evaluating environment policy communication: a case study of the ‘Zero-waste City’ initiative in China - Gong, Ping; Wang, Li; Liu, Xiaolong; Wei, Yigang (Energy, ecology & environment, 2022)
The construction of a ‘zero-waste city’ is a flagship policy to accelerate the development of a green, low-carbon circular economy system in China. Enhancing social participation is an important dimension to evaluate the effect of ‘zero-waste city’ policy construction and an effective way to promote the full achievement of correct waste classification, management, and supervision of solid waste. Based on policy communication theory, this paper aims to take advantage of social media to quantitatively measure the environment policy communication effect and provide a comprehensive panoramic measurement from dynamic characteristics and trend, communication scope, attributes of communicators, and contents dimensions. Based on post data related to ‘zero-waste city’ on Weibo platforms from June 2018 to November 2020, this paper innovatively constructs a measurement system of environmental policy communication that combines social media data with social network analysis and text topic analysis. Results show that from the angle of communication trend, a ‘zero-waste city’ public environment policy is continuously promoted on social media with an increasingly growing volume and is a subject of wide concern for the public. This study confirms the value of social media data in assessing environment policy communication effect and presents several policy implications: Government departments should strengthen environmental policy communication by using Weibo and other social media tools to improve the public’s attention toward the policy and increase their participation in environmental governance; focus on people’s livelihood interest in policy communication content; strengthen the interaction of the public with the content of policies by using a popular and understandable public discourse system and encourage multiple social subjects to participate in policy communication and strengthen the communication of the ‘zero-waste’ cultural concept.